Technique for Diagnosing Cognitive Flexibility in Preschoolers: Comparison of Blank and Digital Forms - Nikolay E. Veraksa; Margarita S. Aslanova; Kristina S. Tarasova; Viktor A. Klimenko (Peoples' Friendship University of Russia (RUDN University), 2023)
Cognitive flexibility is considered a trait of human cognition that helps people adapt to new and changing environments by activating cognitive resources; it develops mainly at preschool age, being a predictor of children's future social and academic successes, which emphasizes the importance of diagnosing its formation. The present study is intended to assess the diagnostic capabilities of the digital version of the Dimensional Change Card Sort technique by P.D. Zelazo aimed at diagnosing the cognitive flexibility of preschoolers, compared with the traditional blank version. The digital version of the technique was tested on a sample of 55 children attending two senior kindergarten groups (57.1% of boys) aged 5 to 6 years (M = 64.03, SD = 2.14). An intra-individual scheme with the division of the subjects into two groups was applied. The first group was initially tested using the blank technique, and a month later using the digital one. The second group, on the contrary, was first tested using the digital technique and, a month later, using the blank one. Thus, the transfer effect was controlled. Sufficient indicators of reliability and consistency of the results of both measurements were obtained for the blank and digital versions of technique. No statistically significant differences were found between the mean values of the same indicators measured by digital and blank techniques different methods (Student's t -test for paired samples). The results of the study show that the digital version of the Dimensional Change Card Sort technique has high indicators of validity and reliability and can be used in diagnostic work. However, these results indicate that the digitalization of techniques cannot always be reduced to a simple translation of them into the form of a software product, and requires additional research when adapting them.